Development of 12-Pulse Regulated Rectifier Circuit for Traction Substation - Sh. N. Nasirov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper proposes a power circuit of a regulated 12-pulse direct current converter and a thyristor control impulse diagram for traction substations providing the best electric power supply of a rolling stock, train traction efficiency,  smooth direction regulation.